O sentido e o significado do ensino médio para os estudantes : um estudo a partir da psicologia histórico-cultural - Melo, Letícia Cavalieri Beiser de (2017)
Historically marked by advances and setbacks, secondary education has been subject of many discussions within the last two decades, which resulted in the definition of several laws, with determinations regarding the offer of seats, teaching modalities and curricular guidelines. Despite this, the challenges to establishing a clear function and identity for this level of education are still huge. The great changes in the work scenario, deriving from the advance of science and technology, began to demand a new type of individual and therefore a new educational process. However, the educational policy available for secondary school, still maintains the old split between theory and practice, and has not been able to meet even the demands of current capitalism, much less to enable the development and emancipation of individuals. In this context, the present research aims at to investigate the sense and meanings of secondary education for students at this level of education, as well as to analyse the similarities and / or differences in students' vision of general and integrated modalities. Beginning from Historical-Cultural Psychology as a theoretical reference and considering that this theory has in Marxian materialism its philosophical basis, which comprehends an individual as a historical partner, who builds reality and is therefore built by it, the method chosen for the investigative process in this dissertation was the historical-dialectical materialism, which allows the understanding of the phenomena in its movement, its historicity and its totality. Based on this framework, it was decided to carry out a theoretical and empirical research, in order to shed light on the research object. In the theoretical study, firstly it was made an analysis of the history of public policies related to secondary school, from the beginning of the twentieth century to the present day, seeking to understand the process of construction of the (social) meaning of secondary school and its relationship with the materiality of each historical time. It was then discussed the understanding of the construction of sense and meanings from Historical-Cultural Psychology, and then the educational assumptions defended in this research were presented, weaving discussions about the function of the school according to Historical-Critical Pedagogy. The empirical research, on the other hand, involved students who were attending secondary school, coming from both the general and the integrated (technical-professional) modalities. The data were collected through interviews based on a semi-structured script and the answers obtained were organized into two thematic axes (I - Secondary school meaning and II - Personal sense of secondary education for the student) to be analysed and discussed. The analyses were based on theorizations of authors who deal with the theme in study or who are linked to the Historical-Cultural Theory. Considering that the appropriation of the method of choice requires, in addition to in-depth studies, a time for elaboration, it is important to highlight that in these analyses it was performed an exercise based on the method of historical-dialectical materialism due to the limitations in terms of methodological domain. The results show that despite the many reformations carried out in secondary school, the duality on its function still persists, so that its meaning is also dual: preparation for graduation studies and preparation for work. This fact reflects the division of classes in our society, so that for the privileged, teaching aims at the University, but, on the other hand, for the working class, it focus on workforce preparation. We also concluded that, since the objectives of secondary education do not focus on the development of the maximum potentialities of individuals, teaching occurs in a superficial and fragmented way, which makes it difficult for students to establish relationships between what they learn and the importance of the content learned for their lives, so that the act of studying becomes meaningless and does not constitute itself as a real activity of study. However, considering the prevailing social meaning about secondary education, and the sense attributed by the students to this phase, we can thus affirm that there is not a split, as there is a general agreement that it should prepare for the future and to obtain a job.